Perbedaan Pengaruh Infusa Kunyit (Curcuma Longa) Dengan Infusa Kelor (Moringa Oleifera) Untuk Pencegahan Kerusakan Pada Organ Lambung, Organ Hati, Organ Ginjal Dan Organ Testis Tikus Yang Diinduksi Acetosal - Joko Santoso; Dwi Retna Prihati; Syahran Wael (Poltekkes Kemenkes Surakarta, 2019)
Background: Continuous use of acetosal can result in an increase in the amount of free radicals in the body which can damage cells. Turmeric contains vitamin C which can neutralize superoxide free radicals, hydrogen, and hydroxyl peroxides. Moringa contains flavonoids which can capture superoxide, peroxide, and hydroxyl free radicals. Objective to see differences in the effect of turmeric and Moringa in preventing cell damage due to acetosal. Method: The research design used was experiment laboratory post-test design. A total of 10 rats were divided into 2 groups. Group 1 (given acetosal (90 mg) / rat and turmeric extract (100 mg / 200 mg BB), group 2 (given acetosal (90 mg) / rat and Moringa extract (200 mg / 200 mg BB). Results: Oral treatment for seven days The results showed turmeric and moringa had the same effect on the prevention of gastric organ damage (p = 1.0), liver (p = 0.4), kidney (p = 0.65) and testicles (p => 5). Conclusion: Turmeric infusion and Moringa infusion are equally good for preventing cell damage.